2020
DOI: 10.1021/acs.iecr.0c01134
|View full text |Cite
|
Sign up to set email alerts
|

Update to “Effect of Temperature and Vapor Residence Time on the Micropyrolysis Products of Waste High Density Polyethylene”

Abstract: A previously published paper presented product composition results in peak area percentage following pyrolysis of waste highdensity polyethylene experiments in a two-stage micropyrolysis reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…261 In PE pyrolysis, early studies showed that only liquid and gas -no wax -are produced above 600 ºC. 265 Increasing temperature leads to increased aromatic production, as gas is converted to aromatics through a Diels-Alder reaction and unimolecular cyclization reactions, [266][267] although a study by Kulas et al 263 showed that the reaction pathway from gas to aromatics has low temperature dependence.…”
Section: Variables Affecting Product Distributionmentioning
confidence: 99%
“…261 In PE pyrolysis, early studies showed that only liquid and gas -no wax -are produced above 600 ºC. 265 Increasing temperature leads to increased aromatic production, as gas is converted to aromatics through a Diels-Alder reaction and unimolecular cyclization reactions, [266][267] although a study by Kulas et al 263 showed that the reaction pathway from gas to aromatics has low temperature dependence.…”
Section: Variables Affecting Product Distributionmentioning
confidence: 99%
“…This means that these reaction pathways have a very low temperature dependence. This is unexpected for k 10 , as the literature shows that increasing temperature has a significant positive effect on aromatic production. , …”
Section: Resultsmentioning
confidence: 87%
“…Going from 550 to 600 °C increased the gas yield from 20 to 30 wt %. Further increases of the reactor temperature up to 675 °C have been found to increase the gas yield up to 80 wt % at a VRT of 1.4 s for waste HDPE . Similar to gas production, aromatic production is also favored at high reaction temperatures (>600 °C).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In PE pyrolysis, early studies showed that only liquid and gas -no wax -are produced above 600 ºC. 246 Increasing temperature leads to increased aromatic production, as gas is converted to aromatics through a Diels-Alder reaction and unimolecular cyclization reactions, [247][248] although a study by Kulas et al 249 showed that the reaction pathway from gas to aromatics has low temperature dependence.…”
Section: Variables Affecting Product Distributionmentioning
confidence: 99%